A Facile Molten‐Salt Route for Large‐Scale Synthesis of NiFe2O4 Nanoplates with Enhanced Lithium Storage Capability. Issue 40 (6th August 2015) - Huang, Gang; Du, Xinchuan; Zhang, Feifei; Yin, Dongming; Wang, Limin
Abstract Binary metal oxides have been deemed as a promising class of electrode materials for high‐performance lithium ion batteries owing to their higher conductivity and electrochemical activity than corresponding monometal oxides. Here, NiFe2O4 nanoplates consisting of nanosized building blocks have been successfully fabricated by a facile, large‐scale NaCl and KCl molten‐salt route, and the changes in the morphology of NiFe2O4 as a function of the molten‐salt amount have been systemically investigated. The results indicate that the molten‐salt amount mainly influences the diameter and thickness of the NiFe2O4 nanoplates as well as the morphology of the nanosized building blocks. Cyclic voltammetry (CV) and galvanostatic charge–discharge measurements have been conducted to evaluate the lithium storage properties of the NiFe2O4 nanoplates prepared with a Ni(NO3)2/Fe(NO3)3/KCl/NaCl molar ratio of 1:2:20:60. A high reversible capacity of 888 mAh g−1 is delivered over 100 cycles at a current density of 100 mA g−1. Even at a current density of 5000 mA g−1, the discharge capacity could still reach 173 mAh g−1. Such excellent electrochemical performances of the NiFe2O4 nanoplates are contributed to the short Li+ diffusion distance of the nanosized building blocks and the synergetic effect of the Ni2+ and Fe3+ ions.